Pengaruh Kepuasan dan Motivasi Kerja terhadap Kinerja Karyawan dengan Organizational Citizenship Behavior (OCB) sebagai Variabel Intervening (Management Analysis Journal, 2015)
The purpose of this study is to determine the influence of job satisfaction, work motivation, and Organizational Citizenship Behavior (OCB)on employees’ performance directly and indirectly that is mediated by Organizational Citizenship Behavior (OCB). The population in this study were all employees of PT Plasa Simpanglima Semarang is 152 employees.Samples used is106 employees.The method of data collection is by quesionares. Data analysis using path analysis. The conclusion of this study areinfluence job satisfaction and work motivation onOCB, the influence OCB on employee performance andOCB has mediate the relationship between job satisfaction and work motivation on employee performance